(untitled) (Communications in Inorganic Synthesis, 2016)
A novel Mn(II) complex with thiosemicarbazone derived from 2-acetylpyridine and N(4)-ethylthiosemicarbazide has been prepared. The single-crystal X-ray analysis of the Mn(II) complex showed a distorted octahedral MnN4S2 environment with the ligand chelating via the nitrogen and sulfur donor atoms in a tridentate manner. The triclinic form of the ligand which has crystallized in a monoclinic system in other works is also described. The basicity ofÂ nitrogen atoms of the ligand was tested with its reaction with HNO3 and the structure of the salt obtained is reported. The result shows that the lone pair of the pyridine nitrogen is more available due to the delocalization of other nitrogen lone pair of electron. Â http://dx.doi.org/10.21060/cis.2016.411